Combined Transplantation of Adipose Tissue-Derived Stem Cells and Endothelial Progenitor Cells Improve Diabetic Erectile Dysfunction in a Rat Model - Qiyun Yang; Wanmei Chen; Chi Zhang; Yun Xie; Yong Gao; Cuncan Deng; Xiangzhou Sun; Guihua Liu; Chunhua Deng (Stem Cells International)
Erectile dysfunction (ED) is a common complication in men suffered with diabetic mellitus. Stem cell transplantation is a promising strategy for the treatment of diabetic ED (DED). In this study, we evaluated whether combined transplantation of adipose tissue-derived stem cells (ADSCs) and endothelial progenitor cells (EPCs) could improve the erectile function of the DED rat model. DED rats were induced via intraperitoneal injection of streptozotocin (50 mg/kg), and ED was screened by apomorphine (100 mg/kg). DED rats were divided into 4 groups (n=14 each): DED, ADSC, EPC, and ADSC/EPC group. Another 14 age-matched male SD rats with normal erectile function were served as the normal group. The normal group and the DED group were received intracavernous injection with phosphate-buffered saline (PBS). And the other groups were received intracavernous injection with ADSCs (1×106), EPCs (1×106), and ADSCs/EPCs (0.5×106/0.5×106), respectively. The total intracavernous pressure (ICP) and mean arterial pressure (MAP) were recorded at day 28 after injection. The endothelium, smooth muscle, and penile dorsal nerves were assessed within cavernoursal tissue. On day 28 after injection, the ADSC/EPC group displayed more significantly enhanced ICP and ICP/MAP than the DED or ADSC or EPC group (p<0.05). Immunofluorescent analysis and western blot demonstrated that the improvement of erectile function in the ADSC/EPC5 group was associated with increased expression of endothelial marker (CD31) and the correction of eNOS-cGMP-NO signaling. More 5-ethynyl-2′-deoxyuridine- (EdU-) positive EPCs could be found lining in the cavernous endothelial layer in the ADSC/EPC group than the EPC group, which was attributed to the paracrine of vascular endothelial growth factor (VEGF) and stromal-derived factor-1 (SDF-1) by ADSCs. Combined transplantation of ADSCs and EPCs has a synergic effect in repairing the endothelial function of DED rats, and the underlying mechanism might be the paracrine of VEGF and SDF-1 by ADSCs, which improves the recruitment and proliferation of EPCs in the cavernosum.